Genetic diversity analysis for wild and cultivated accessions of Cymbopogon citratus (D.C.) Stapf using phytochemical and molecular markers - Bushra Shamsheer; Nadia Riaz; Zubaida Yousaf; Sajjad Hyder; Arusa Aftab; Rashid Iqbal; Muhammad Habib ur Rahman; Ibrahim Al-Ashkar; Khalid F. Almutairi; Ayman El Sabagh (PeerJ, 2022)
Background Genetic diversity is being lost because of increasing urbanization and decreasing cultivation land, which leads to the abrupt use of wild resources of medicinally aromatic plants (MAPs). Cymbopogon citratus is a morphologically diverse MAP that is largely exploited in the food, cosmetics, and pharmaceutical industries. However, the intraspecific phytochemical and molecular diversity of C. citratus has yet to be explored. Methodology The germplasm was obtained from four different countries representing Pakistan, India, Bangladesh, and the United States. Oil extraction was performed by hydro distillation, and metabolic profiles of different accessions were generated by GC–MS. Seventeen functional molecular markers based on three genes encoding cytochrome P450, uridyl diphosphate glycosyltransferase and the 5S rRNA gene family were used to explore genetic diversity. Principal component analysis (PCA) and heatmaps were constructed using R software with the help of the gg-plot R package v1.0.5 for data validation. Results Among the 208 identified metabolites, citral was maximal, with a phytochemical contribution (1.92–27.73%), α-pinene (0.82–15.57%), verbenol (0.24–22.84%), neral (0.23–21.31%) and geranial acetate (0.43–15.65%). In the majority of accessions, citral was the dominant component. The highest concentration of citral was detected in 384541 (27.74%), 384527 (27.52%) belonging to Pakistan and one USA-based accession 38456 (27.71%). Region-specific grouping revealed a relationship between genetic diversity and geographical location. Pakistani accessions 384518, 38452, and 384544 genetically and 384535, 384518, and 384510 were phytochemically diverse. Conclusion The genetic diversity was more pronounced in cultivated accessions than in wild accessions. Moreover, it was observed that phytochemical diversity correlated with the altitude and temperature of the region.